Sustainability and Environmental Impact of Polymer Concrete with Styrene Monomer and GGBFS In Structural Applications: A Literature Review - Nursamhuda, Wahyu; Susanti, Lilya; Wijaya, Ming Narto (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Polymer concrete using styrene monomer and Ground Granulated Blast Furnace Slag (GGBFS) as key components show great potential in sustainability and environmental impact for structural applications. This study examines its ability to reduce carbon emissions, improve energy efficiency through recycled materials, and reduce reliance on Portland cement. Using styrene monomer enhances resistance to corrosion and cracking but also presents challenges related to volatile organic compound (VOC) emissions, which are harmful to the environment. The literature review concludes that although this polymer concrete shows promise as an environmentally friendly material, further development is needed to address sustainability challenges, particularly in production and material recycling processes. Additional research is required to overcome production efficiency and material recycling challenges.